ANALYSIS OF HUMAN HISTORY AND APPROACHES TO IT - Temirova Svetlana Vladimirovna (American Journals Publishing, 2023)
In the modern period in the world, especially during the period of fundamental changes in the life of our country, social consciousness and its manifestations, features of social consciousness, its forms, everyday consciousness, customs, traditions, beliefs, theoretical consciousness, a system of ideas, concepts, laws and other forms spirituality, as well as the transformation of each theory and idea into mass consciousness and its characteristics, Social psychology (psyche), Ideology (ideology). Features of the spontaneous formation of social psychology in people, the emergence of legal consciousness along with the state, the introduction of it by the state as a norm of behavior. Legal consciousness is analyzed through its forms and teachings of the peoples of Central Asia.
Keywords: Civilization, public consciousness, everyday consciousness, public consciousness, social psychology, ideology, legal consciousness, state, behavior.